The Influence of Product Quality on Customer Loyalty with Customer Satisfaction as a Mediating Variable among Gen Z Consumers of Kopi Kenangan in Makassar City - Nur Azizah; Anwar; Muhammad Ichwan Musa; Muhammad Ilham Wardhana; Nurul Fadilah Aswar (PT. Maju Malaqbi Makkarana, 2026)
The Effect of Product Quality on Customer Loyalty with Customer Satisfaction as a Mediating Variable among Gen Z Consumers of Kopi Kenangan in Makassar City. Thesis, Departement of Management, Faculty of Economies and Bussiness. State University of Makassar. Supervised by Mr. Anwar and Mr. Muhammad Ichwan Musa. This study aims to determine the effect of product quality on customer loyalty with customer satisfaction as a mediating variable among Generation Z consumers of Kopi Kenangan in Makassar City. The focus of this research is to analyze how product quality can increase customer satisfaction and shape customer loyalty. This research uses a quantitative approach with an associative explanatory design. Data were collected through questionnaires distributed to 110 respondents who are Gen Z consumers of Kopi Kenangan in Makassar City. The data analysis technique used Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS version 4.0.9.9 to examine the relationships among variables. The results show that product quality has a positive and significant effect on customer satisfaction and customer loyalty. Customer satisfaction also has a positive and significant effect on customer loyalty and acts as a mediating variable in the relationship between product quality and customer loyalty. These findings indicate that good product quality can increase customer satisfaction and strengthen customer loyalty to Kopi Kenangan in Makassar City